The relationship between innovation and performance in MSMEs: The case of the wearing apparel sector in emerging countries - Larios Francia, Rosa Patricia (2023)
In a global context of change and uncertainty, the innovation capacity of organizations is key to their sustained development. The objective of this study is to empirically analyze the relationship between innovation and firm performance of micro, small and medium-sized enterprises (MSMEs) in emerging countries and to study the moderating role of investment and collaboration in these relationships. The least squares structural equation model (PLS-SEM) analyzed a sample of 104 SMEs in the wearing apparel sector in Peru and Colombia. Product Innovation together with Business Process Innovation, explained 47.1 % of organizational performance, 41.0 % of economic performance, 39.5 % of commercial performance and 36.9 % of productive performance. However, Product Innovation was not a significant predictor of productive or organizational performance. The moderating effect of Investment on the relationship between Product Innovation and Business Process Innovation and Firm performance was only significant for organizational and productive performance and with respect to the moderating effect of Collaboration on the relationship between Product innovation and Business Process Innovation and Firm performance, in the quantitative analysis no significant prediction was obtained, supported by the results of the surveys where 62.8 % of the MSMEs never received supported from others actors for the development of innovation activities. The application of the findings of this study can contribute to the validation, updating or implementation of public policies that promote collaboration between actors of the innovation ecosystem, as well as in proposal of investment strategies for the development of innovation in emerging countries.